Daily rests of wild boar Sus scrofa sows in southern Sweden - Persson, Charlie (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2010)
For a few decades, the wild boars are established over large areas in southern and central Sweden. Where they cause problems in terms of damage to crops in the agriculture landscape, where rooting, browsing and trampling, but also damage to the crop when wild boars chosen daily rest in the cultivated fields. Along with the growing number of wild boars the rate of car accident with wild boars has also increased.